1980
DOI: 10.1002/nur.4770030304
|View full text |Cite
|
Sign up to set email alerts
|

Needs assessment for hospital‐based home care services

Abstract: Careful needs assessment is a prerequisite to addressing issues of health care program effectiveness and program planning from a population-based perspective. Home care program evaluation literature is lacking in examples of strategies for such assessment. A nurse-screening of admissions was conducted at an acute care general hospital to estimate need for hospital-based home care (HBHC) services among the 2,613 patients discharged from medical and surgical services over a 5-month period. After careful delineat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

1987
1987
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
1
0
3
Order By: Relevance
“…No levantamento bibliográfico, o estudo de Inui et al (11) , identifica a adequação das indicações da equipe de assistência domiciliária de um hospital para pacientes ao programa de AD. Conclui que a técnica de avaliação apresentada, embora confiável, demandava um custo elevado, pela exigência de juízes, enfermeiras com habilidades clínicas e com experiência relevante anterior.…”
Section: Resultsunclassified
“…No levantamento bibliográfico, o estudo de Inui et al (11) , identifica a adequação das indicações da equipe de assistência domiciliária de um hospital para pacientes ao programa de AD. Conclui que a técnica de avaliação apresentada, embora confiável, demandava um custo elevado, pela exigência de juízes, enfermeiras com habilidades clínicas e com experiência relevante anterior.…”
Section: Resultsunclassified
“…Our original goal in this research was to examine the impact of the Medicare prospective payment plan on a home health service in a teaching hospital; however, before such a study could be conducted, it was necessary to develop and validate an instrument for gathering data, as one could not be found in the literature that was applicable in this study. A review of the literature revealed only one paper in which psychometric research consisting of validity or reliability studies had been conducted on the instrument itself prior to its use in assessing patient need for home care (Inui, Stevenson, Plorde, & Murphy, 1980). That study and the present one differ in several respects.…”
mentioning
confidence: 74%
“…No levantamento bibliográfico dos últimos 20 anos, os estudos reconhecem muito mais o perfil do paciente que necessita da assistência de enfermagem domiciliar, do que a quantificação da demanda do cuidado no momento da alta hospitalar (11)(12) .…”
Section: Introductionunclassified